Determinasi Capaian Pembangunan Desa di Sumatera Barat: Bukti Empiris dari Efektivitas Dana Desa, Efisiensi Belanja Modal, dan Kapasitas Fiskal Daerah - Halkadri Fitra; Muhammad Nadhif Faridzan; Salma Taqwa; Dewi Pebriyani; Vita Fitria Sari; Fefri Indra Arza (Jurnal Eksplorasi Akuntansi, 2026)
Fiscal decentralization implemented through the Village Fund program is expected to promote sustainable improvements in village development. This study examines the effects of Village Fund utilization effectiveness, capital expenditure efficiency, and regional fiscal capacity on village development performance, as measured by the Village Development Index (IDM), in West Sumatra Province. A quantitative causal research design was employed, using panel data regression analysis to assess the relationships among the variables. The results indicate that the effectiveness of Village Fund utilization does not have a statistically significant impact on the IDM. In contrast, capital expenditure efficiency and regional fiscal capacity exhibit positive and significant effects on village development outcomes. These findings suggest that development performance is driven more by the quality of budget management and the strength of regional fiscal capacity than by budget absorption levels alone. From a theoretical perspective, this study reinforces the relevance of the value for money principle and the capacity-based development approach in village development studies. In practical terms, the findings highlight the need for local governments to prioritize improvements in spending efficiency and fiscal capacity in order to enhance the developmental impact of Village Funds.